Economic analysis of Agaricus bisporus mushrooms production and the perspective of sharing economy - Schilla, Filip; Prochazka, Petr; Mumladze, Gaga; Soukupova, Jana; Smutka, Lubos (Frontiers in Sustainable Food Systems, 2025)
Introduction Urban agriculture, particularly mushroom cultivation in basements, offers a sustainable solution to climate change, land scarcity, and food security challenges. This article explores the viability of cultivating Agaricus bisporus (white button mushrooms) in basements, while also considering the potential of a sharing economy business model to address these issues. Methods We simulate basement and ground-level room conditions, comparing factors such as temperature, humidity, light exposure, and air quality, which are crucial for mushroom growth. Economic calculations are also included to assess costs and profits, allowing for a comparison of feasibility and cost-effectiveness between the two environments. Results The basement environment proves more favorable for mushroom cultivation, with stable temperatures and higher humidity reducing energy requirements. Economic analysis shows that basement cultivation has lower initial and operational costs compared to ground-level spaces. Discussion Basement cultivation of Agaricus bisporus offers a sustainable solution for urban agriculture, addressing food security and land scarcity. Integrating this practice into a sharing economy model could further enhance its feasibility, contributing to environmental sustainability and economic growth in cities.